2013
DOI: 10.1080/09540121.2013.855700
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer incidence and screening in US Medicaid patients with and without HIV infection

Abstract: Non-AIDS defining malignancies, particularly colorectal cancer (CRC), may be more prevalent among persons living with HIV (PLWH). Further, PLWH may be less likely to receive CRC screening (CRCS). We studied the epidemiology of CRC and CRCS patterns in patients with and without HIV in a large US Medicaid population. We performed a matched cohort study examining CRC incidence in 2006 and CRCS between 1999 and 2007. Study participants were continuously enrolled in the Medicaid programs of California, Florida, New… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 25 publications
4
12
0
Order By: Relevance
“…However, two studies have reported that colorectal cancer screening rates in PLWH are 20% lower than in the general population. 74,75 Increasing PLWH participation in colorectal cancer screening would be expected to improve their survival.…”
Section: Site-specific Screening Approachmentioning
confidence: 99%
“…However, two studies have reported that colorectal cancer screening rates in PLWH are 20% lower than in the general population. 74,75 Increasing PLWH participation in colorectal cancer screening would be expected to improve their survival.…”
Section: Site-specific Screening Approachmentioning
confidence: 99%
“…In single-centre studies, the proportions of persons with HIV aged 50 years and older who received colorectal cancer screening has ranged from 46.9% to 55.6% [ 14 - 17 ]. In a large study using United States Medicaid claims data on beneficiaries in five states, only 35.8% of 22,928 age-eligible persons with HIV underwent colorectal cancer screening between 1999 and 2007 [ 18 ]. However, these findings likely underestimate the extent of screening somewhat because claims for fecal occult blood testing were not examined in this study [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a large study using United States Medicaid claims data on beneficiaries in five states, only 35.8% of 22,928 age-eligible persons with HIV underwent colorectal cancer screening between 1999 and 2007 [ 18 ]. However, these findings likely underestimate the extent of screening somewhat because claims for fecal occult blood testing were not examined in this study [ 18 ]. Nonetheless, taken as a whole, the existing evidence suggests that efforts to improve colorectal cancer screening rates in persons with HIV are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with HIV-uninfected patients, PLWHA may be screened and treated for NCDs at lower rates[10, 13, 27, 28]. ID providers report less comfort managing diabetes (DM), hypertension (HTN), hyperlipidemia (HL) and depression than generalists[29] and have four times increased odds of referring for HTN or DM management[30].…”
Section: Introductionmentioning
confidence: 99%